One-Pot Synthesis of Bisindolylmethanes from Benzyl Alcohols and Indoles Using Catalytic Iodine and Molecular Oxygen under Visible Light Irradiation - Nobuta, Tomoya; Fujiya, Akitoshi; Tada, Norihiro; Miura, Tsuyoshi; Itoh, Akichika (Synlett, 2012)
Bisindolylmethanes can be directly synthesized from benzyl alcohol and indole in up to 86% yield using molecular oxygen, visible light, and catalytic iodine, which serves as both an oxidant and a Lewis acid.
Keywords: photooxidation; iodine; molecular oxygen; bisindolylmethane; benzyl alcohol